The confidence effects of fiscal consolidations - Roel Beetsma; Jacopo Cimadomo; Oana Furtuna; Massimo Giuliodori (European Central Bank (ECB), 2015)
We explore how fiscal consolidations affect private sector confidence, a possible channel for the fiscal transmission that has received particular attention recently as a result of governments embarking on austerity trajectories in the aftermath of the crisis. Panel regressions based on the action-based datasets of De Vries et al. (2011) and Alesina et al. (2014) show that consolidations, and in particular their unanticipated components affect confidence negatively. The effects are stronger for revenue-based measures and when institutional arrangements, such as fiscal rules, are weak. To obtain a more accurate picture of how consolidations affect confidence, we construct a monthly dataset of consolidation announcements based on the aforementioned datasets, so that we can study the confidence effects in real time using an event study. Consumer confidence falls around announcements of consolidation measures, an effect driven by revenue-based measures. Moreover, the effects are most relevant for European countries with weak institutional arrangements, as measured by the tightness of fiscal rules or budgetary transparency. The effects on producer confidence are generally similar, but weaker than for consumer confidence. Long-term interest rates, as a measure of confidence in the sovereign, tend to fall around spending-based consolidation announcements that take place in slump periods. Overall, if confidence is a concern and consolidation is unavoidable, spending-based measures seem preferable. Slump periods are not necessarily bad moments for such measures, while strengthening institutional arrangements may help in mitigating adverse confidence effects.
Keywords: H60; H61; H62; 330; announcements; consolidation plans; consumer- and business confidence; Event study; institutional quality; long-term interest rates; revenues; spending; Haushaltskonsolidierung; Konsumentenverhalten; Vertrauen; Sparen; Privater Haushalt; Ereignisstudie; OECD-Staaten